Influence of long-term fertilization on soil aggregates stability and organic carbon occurrence characteristics in karst yellow soil of Southwest China - Liu, Yanling; Zhang, Meng; Xiong, Han; Li, Yu; Zhang, Yarong; Huang, Xingcheng; Yang, Yehua; Zhu, Huaqing; Jiang, Taiming (Frontiers in Plant Science, 2023)
Current research has long focused on soil organic carbon and soil aggregates stability. However, the effects of different long-term fertilization on the composition of yellow soil aggregates and the characteristics of the occurrence of organic carbon in the karst region of Southwest China are still unclear. Based on a 25-year long-term located experiment on yellow soil, soil samples from the 0–20 cm soil layer were collected and treated with different fertilizers (CK: unfertilized control; NPK: chemical fertilizer; 1/4 M + 3/4 NP: 25% chemical fertilizer replaced by 25% organic fertilizer; 1/2 M + 1/2 NP: 50% chemical fertilizer replaced by organic fertilizer; and M: organic fertilizer). In water-stable aggregates, soil aggregates stability, total organic carbon (TOC), easily oxidized organic carbon (EOC), carbon preservation capacity (CPC), and carbon pool management index (CPMI) were analyzed. The findings demonstrated that the order of the average weight diameter (MWD), geometric mean diameter (GWD), and macro-aggregate content (R0.25) of stable water aggregates was M > CK > 1/2M +1/2NP > 1/4M +3/4NP> NPK. The MWD, GWD, and R0.25 of NPK treatment significantly decreased by 32.6%, 43.2%, and 7.0 percentage points, respectively, compared to CK treatment. The order of TOC and EOC content in aggregates of different particle sizes was M > 1/2M +1/2NP > 1/4M +3/4NP> CK > NPK, and it increased as the rate of organic fertilizer increased. In macro-aggregates and bulk soil, the CPC of TOC (TOPC) and EOC (EOPC), as well as CPMI, were arranged as M > 1/2M +1/2NP > 1/4M +3/4NP> CK > NPK, but the opposite was true for micro-aggregates. In bulk soil treated with organic fertilizer, the TOPC, EOPC, and CPMI significantly increased by 27.4%–53.8%, 29.7%–78.1%, 29.7–82.2 percentage points, respectively, compared to NPK treatment. Redundancy analysis and stepwise regression analysis show that TOC was the main physical and chemical factor affecting the aggregates stability, and the TOPC in micro-aggregates has the most direct impact. In conclusion, the primary cause of the decrease in SOC caused by the long-term application of chemical fertilizer was the loss of organic carbon in macro-aggregates. An essential method to increase soil nutrient supply and improve yellow soil productivity was to apply an organic fertilizer to increase aggregates stability, storage and activity of SOC in macro-aggregates.